Analisis Yuridis Putusan Nomor 509/Pid.Sus/2023/PN Mjk Terhadap Korban Penyalahgunaan Narkotika di Mojokerto - Rizkie Erviana Suryasari; Wahyu Prawesthi; Bahrul Amiq (Politika Progresif : Jurnal Hukum, Politik dan Humaniora, 2025)
Narcotics abuse is a serious problem that threatens the security and welfare of society. This thesis aims to carry out a juridical analysis of the decision of the Mojokerto District Court Number 509/Pid.Sus/2023/PN Mjk, which handles narcotics abuse cases, with a focus on the Narcotics Law. This thesis examines how the decision provides justice to victims of narcotics abuse in Mojokerto. The analysis involves legal interpretation, legal considerations, and the impact of applying the article on the victim. Apart from that, this thesis also discusses the extent to which this decision can contribute to efforts to prevent narcotics abuse in society.The research method used is an empirical method with document analysis, which includes a study of Mojokerto District Court decisions, laws and related literature. The results of an in-depth analysis of the decision show an understanding of the rights and legal protection for victims of narcotics abuse, especially by detailing aspects related to Articles 112 and 114 of the Narcotics Law.The results of this research are as follows (1). The basis for the judge's decision is case Number 509/Pid.Sus/2023/PN Mjk which is articles 112 and 114 of the Narcotics Law. Where the judge decided on a criminal sentence of 9 years (2). The decision given by the judge was correct, based on articles 112 and 114 of the Narcotics Law. Namely a prison sentence of 9 years. Articles 112 and 114 regulate criminal sanctions for narcotics abusers.